The impact of information sphere in the economic security of the country: Case of Russian realities - Igor Okhrimenko; Valery Stepenko; Olga Chernova; Elena Zatsarinnaya (Journal of Innovation and Entrepreneurship, 2023)
Novel information technologies have facilitated not only the development of new industries, but also brought new opportunities and challenges. The range of challenges includes threats related to the information security of not only the commercial, but also the public sector of the national economy, which can adversely affect its stability and competitiveness. In view of this, the problem of ensuring information security (IS) in the economic sphere is of particular relevance. Despite the abundance of studies on IS, the impact of the information sphere on the country's economic security has not yet been sufficiently studied. The purpose of this article was to identify and systematize threats posed to economic security by the information environment and determine a set of measures to protect the areas at risk. Within the framework of the study, two interrelated models were built. The first systematized the IS threats and challenges, whereas the second demonstrated those IS threats that are directly connected with the state's economic security. At the same time, the models developed allowed focusing on the protection of objects potentially under threat. The research quintessence was represented by the development of recommendations directed at preventing and minimizing the negative impact of information sphere threats to economic security. Hence, a diversified ecosystem of information and economic security of the state was created. The study findings and recommendations can be used by officials of government bodies and other organizations to develop regulatory documents related to the strategy of ensuring information and economic security at various levels (state, regional, corporate).
Keywords: 650; Cybercrime; Information and communications technologies; Information security; Informatization; Security strategy